2012
DOI: 10.1183/09031936.00065212
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of in-hospital death from community-acquired pneumonia by varying CRB-age groups

Abstract: C(U)RB-65 (confusion, (urea .7 mol?L -1 ,) respiratory frequency o30 breaths?min -1 , systolic blood pressure ,90 mmHg or diastolic blood pressure f60 mmHg and age o65 years) is now the generally accepted severity score for patients with community-acquired pneumonia (CAP) in Europe.In an observational study based on the large database from the German nationwide performance measurement programme in healthcare quality, including data from all hospitalised patients with CAP during 2008-2010, different CRB-age gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
2
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 23 publications
(35 reference statements)
2
35
2
9
Order By: Relevance
“…Two new scoring categories have since been proposed, extending the age and urea criteria to ≥85 years and ≥11 mmol/L, respectively, and with each scoring two points. Both cut-off points are considered to correlate with mortality 9 16 25. Extending the already adopted urea and age criteria allows a simple transition towards the use of the CURB-age score.…”
Section: Discussionmentioning
confidence: 99%
“…Two new scoring categories have since been proposed, extending the age and urea criteria to ≥85 years and ≥11 mmol/L, respectively, and with each scoring two points. Both cut-off points are considered to correlate with mortality 9 16 25. Extending the already adopted urea and age criteria allows a simple transition towards the use of the CURB-age score.…”
Section: Discussionmentioning
confidence: 99%
“…Established risk stratification tools like the CRB-65 and PSI scores work less well in elderly and severely disabled patients, but can be significantly improved by including oxygenation measurement and assessment of functional status [47][48][49][50]. A recent population-based study from Germany showed that especially the negative predictive value of the CRB-65 score for mortality in nursing home patients is insufficient as hospital mortality of identified ''low risk'' patients was still about 20%, but prediction could be improved by the evaluation of functional status (''bedridden'') and comorbidities [50].…”
Section: Risk Of Unstable Comorbiditiesmentioning
confidence: 99%
“…[2345678910] Most of the patients were males, average age 63.7 years, smokers with co-morbidities. Over 88% of investigated patients had co-morbidity, mainly cardiovascular (53.4%).…”
Section: Discussionmentioning
confidence: 99%
“…Major risk scores (PSI, CURB65) have shown to be significant advance in prediction of mortality due to CAP. [123456789] However, there are some important issues with the risk scores. PSI is more suitable for identification of low risk patients benefiting from outpatient treatment whereas CURB65 improves identification of high risk patients.…”
mentioning
confidence: 99%